تفسیری ادب کی روشنی میں یہود ونصارٰی کے اختلافات:حقیقت و نوعیت: Essentiality and Nature of Discrepancy among Doctrinaire (An Abstraction of Tafseeri Dissertation) - Dr. Muhammad SamiUllah; Faiqa Imran (MEI, 2023)
Christian and Jews are named as Doctrinaire by Holy Quran. Ostensibly they are Islam friendly adversaries but the facts are far yonder as they are the brinks that never get unite. They not only have dissensions in legal maxims but are also antagonistic in several other negotiations. Descriptive study method will be used to check an account for all the discords among apostles. The research study will end up highlighting the nature and essentiality of the cardinal discrepancies in the ablaze of various Tafseeric compositions.